2019
DOI: 10.1016/j.ijpam.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired urinary tract infections in children

Abstract: Objective The aim of the present study was to investigate the bacterial pathogens and their resistance patterns in children presenting with their first admission for a urinary tract infection (UTI) in a large tertiary care center in Riyadh, Saudi Arabia. Methods A retrospective chart review was conducted of pediatric patients 0–14 years of age who were admitted for their first community-acquired UTI in a large tertiary care center in Riyadh, Saudi Arabia. The review cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
39
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(72 citation statements)
references
References 15 publications
8
39
4
2
Order By: Relevance
“…E. coli was the most common prevalent pathogen isolated from UTI patients in the current study, E. coli have been implicated in 56 samples (45.90%), this finding accords many studies [23,24], also agree with [25] that mentioned E. coli prevalence was (42.2%) in patients with UTI. Followed by Enterobacter species 23% of total urine samples and these findings were in agreement with other respective studies conducted elsewhere [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…E. coli was the most common prevalent pathogen isolated from UTI patients in the current study, E. coli have been implicated in 56 samples (45.90%), this finding accords many studies [23,24], also agree with [25] that mentioned E. coli prevalence was (42.2%) in patients with UTI. Followed by Enterobacter species 23% of total urine samples and these findings were in agreement with other respective studies conducted elsewhere [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…Isolates expressing various ESBLs were confirmed by double-disk potentiation method, thirteen studies from Saudi Arabia reported the phenotypic prevalence of ESBLs in E. coli and ESKAPE pathogens. These studies showed that during the initial study period of year 2000, ESBL prevalence was relatively low (4.8%), but increased dramatically to 72% by 2020 in these countries based on the data obtained from 93,961 clinical samples [ 13 , 14 , 19 , 20 , 22 , 24 , 25 , 28 , 29 , 30 , 31 , 32 , 33 ]. The PCR analysis of various β-lactamases traits shown in Table 2 indicates that the prevalence of bla SHV , bla TEM and bla CTX-M among the E. coli and ESKAPE pathogens increased from between 2.6–8.5 to 84.1–97.3%, the bla OXA, enzyme during this period increased from 26.2% to 85.7%, and increasing resistance for bla PER bla GES β-lactamases was also demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Followed by Enterobacter species 23% of total urine samples and these findings were in agreement with other respective studies conducted elsewhere. [30][31] The age group 21-40 years was the most common infected group 47%. [29] followed by the age group less than 20 years 29%.…”
Section: Resultsmentioning
confidence: 99%